Relationship of family functioning and attachment in school adolescents of a Public Educational Institution of Ate - Perotti Maiocchi, Gabriella Francesca (2021)
The objective of this research is to determine the relationship between Family Functioning and Attachment in school adolescents of a Public Educational Institution in Ate. The study belongs to the descriptive level, of a quantitative type and with a non-experimental, cross-correlational design. The sample was made up of 139 school adolescents, of both sexes, between 12 to 17 years of age, enrolled from the 1st to the 5th year of secondary school. The Epstein, Baldwin, and Bishop Family Assessment Device (FAD), and the Armsden and Greenberg Inventory of Parent and Peer Attachment (IPPA), were applied. The results corroborate that there is a significant relationship between Family Functioning and Attachment in this group of school adolescents. The correlation is significant, weak, and direct between Family Functioning and Attachment with mother and father and is moderate and direct with peers.